2022
DOI: 10.3390/ma15062203
|View full text |Cite
|
Sign up to set email alerts
|

Graphene as a Transparent Conductive Electrode in GaN-Based LEDs

Abstract: Graphene combines high conductivity (sheet resistance down to a few hundred Ω/sq and even less) with high transparency (>90%) and thus exhibits a huge application potential as a transparent conductive electrode in gallium nitride (GaN)-based light-emitting diodes (LEDs), being an economical alternative to common indium-based solutions. Here, we present an overview of the state-of-the-art graphene-based transparent conductive electrodes in GaN-based LEDs. The focus is placed on the manufacturing progress and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 111 publications
0
12
0
Order By: Relevance
“…Work function ~ 4.0 eV ~7.5 eV ~ 4.47 eV cause an increase in its sheet resistance due to an increase in carrier scattering [18], [38], [81], [82]. emitting at 456 nm [27].…”
Section: Materials N-gan P-gan Pristine Graphenementioning
confidence: 99%
“…Work function ~ 4.0 eV ~7.5 eV ~ 4.47 eV cause an increase in its sheet resistance due to an increase in carrier scattering [18], [38], [81], [82]. emitting at 456 nm [27].…”
Section: Materials N-gan P-gan Pristine Graphenementioning
confidence: 99%
“…This development will not only impact photovoltaics but also other devices such as LEDs, where strong progresses have been made in the use of 2D materials‐based TCE. [ 178 ] Moreover, the development of TCE at industrial level is now considered, and scalable production have been already demonstrated. [ 179 ]…”
Section: Perspectives On Future Materials For Space Pvmentioning
confidence: 99%
“…This development will not only impact photovoltaics but also other devices such as LEDs, where strong progresses have been made in the use of 2D materials-based TCE. [178] Moreover, the development of TCE at industrial level is now considered, and scalable production have been already demonstrated. [179] Concomitantly, 2D materials have been tested (on Earth) in space-relevant conditions as components of electronic devices such as transistors, sensors, etc.…”
Section: Perspectives On Future Materials For Space Pvmentioning
confidence: 99%
“…Researchers have developed a number of strategies to displace incumbent ITO, including TCEs based on metal oxides 4 , 5 , carbon nanotubes 6 , 7 , graphene 8 , 9 , conductive polymers 10 , 11 , oxide/metal/oxide strutures 12 15 , and metal nanowire networks 15 19 . Metal nanowire networks are promising due to their high performance, high scalability, low cost, and flexibility 20 , 21 .…”
Section: Introductionmentioning
confidence: 99%